Study of clinical features, haematological changes and outcome in snake bite cases - Theng, Shubham P.; Khyalappa , Rajesh J. (International Journal of Research in Medical Sciences, 2024)
Background: Snake bite is a common acute medical emergency faced by rural populations in tropical and subtropical countries. In India, a large proportion of snake bites occur when people are working barefoot in the fields or while walking at night. More than 2,000 species of snakes are known worldwide, of which around 400 are poisonous. These snakes belong to the families Elapidae, Viperidae, Hydrophiidae and Colubridae. Methods: A prospective was done at medicine department of SDH Sawantwadi, Sindhudurgh. Study duration was 3 months (May 2023 to July 2023). Study population included all cases admitted in SDH Sawantwadi with history of snake bite. Sample size was 50. Results: Majority of cases found in the age group of 18-30 years 19 cases (38%) followed by 9 cases in 31-45 age group, 12 in 46-60 age group and 10 cases in 61 and above group. Majority of patients with history of snake bite were males contributing 27 (54%). Snake bites were more common in males as compared to females 23 (46%). 14% snake bite cases have activated partial thromboplastin time (APTT) >30 seconds, 10% of snake bite cases had prothrombin time (PT) >15 sec, 30% had platelet count <100000, increased leucocyte count >11000 was seen in 22% cases and 12% victims showed whole blood clotting test (WBCT) >20 minutes. Clinical outcome was 90% discharged after treatment and 10% death during treatment. Correlation between PT and clinical outcome is significant at p<0.5. Conclusions: Association between PT and mortality among snake bite patients was statistically significant.